Surgical safety and effectiveness of bilateral axillo-breast approach robotic thyroidectomy: a systematic review and meta-analysis - Yun Jin Kang; Gulnaz Stybayeva; Se Hwan Hwang (Brazilian Journal of Otorhinolaryngology, 2024)
Objectives: To assess the safety and effectiveness of bilateral axillo-breast approach robotic thyroidectomy in thyroid tumor. Methods: Bilateral axillo-breast approach robotic thyroidectomy and other approaches (open thyroidectomy, transoral robotic thyroidectomy, and bilateral axillo-breast approach endoscopic thyroidectomy) were compared in studies from 6 databases. Results: Twenty-two studies (8830 individuals) were included. Bilateral axillo-breast approach robotic thyroidectomy had longer operation time, greater cosmetic satisfaction, and reduced transient hypoparathyroidism than conventional open thyroidectomy. Compared to bilateral axillo-breast approach endoscopic thyroidectomy, bilateral axillo-breast approach robotic thyroidectomy had greater amount of drainage, lower chances of transient vocal cord palsy and permanent hypothyroidism, and better surgical completeness (postopertive thyroblobulin level and lymph node removal). Bilateral axillo-breast approach robotic thyroidectomy induced greater postoperative drainage and greater patient dissatisfaction than transoral robotic thyroidectomy. Conclusion: Bilateral axillo-breast approach robotic thyroidectomy is inferior to transoral robotic thyroidectomy in drainage and cosmetic satisfaction but superior to bilateral axillo-breast approach endoscopic thyroidectomy in surgical performance. Its operation time is longer, but its cosmetic satisfaction is higher than open thyroidectomy.